Accumulation of perfluoroalkyl acids as forever chemicals in Antarctic waters - Núria Trilla-Prieto; Jordi Dachs; Jon Iriarte; Naiara Berrojalbiz; Pere Colomer-Vidal; Gemma Casas; Odei Garcia-Garin; Maria Vila-Costa; Begoña Jiménez (Communications Earth & Environment)
Abstract Perfluoroalkyl acids have been widely used during the last fifty years in a myriad of industrial and consumer applications, and are a paradigm of persistent “forever chemicals”. Earlier studies suggested a limited occurrence in the Southern Ocean as a consequence of the Antarctic circumpolar current preventing their oceanic transport southwards. Here we show perfluoroalkyl acids in the Bransfield Strait and Bellingshausen Sea (west of Antarctic Peninsula) at concentrations of comparable magnitude to those measured in the North Atlantic, a region impacted by historical sources. Atmospheric wet deposition of perfluoroalkyl acids previously aerosolized by sea-spray arises as the perfluoroalkyl acids source to Antarctica. The prevailing marine and atmospheric circulation in the region encapsulate these chemicals in the Antarctic region once these have crossed the Antarctic divergence. This work underscores the importance of persistence driving chemical’s environmental risk, and raises concern on the impact of the larger pool of per- and polyfluoroalkyl substances.